2009
DOI: 10.1007/s11095-009-9976-1
|View full text |Cite
|
Sign up to set email alerts
|

“Soft” Calcium Crosslinks Enable Highly Efficient Gene Transfection Using TAT Peptide

Abstract: Purpose Typically, low molecular weight cationic peptides or polymers exhibit poor transfection efficiency due to an inability to condense plasmid DNA into small nanoparticles. Here, efficient gene delivery was attained using TAT/pDNA complexes containing calcium crosslinks. Methods Electrostatic complexes of pDNA with TAT or PEI were studied with increasing calcium concentration. Gel electrophoresis was used to determine DNA condensation. The morphology of the complexes was probed by transmission electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(73 citation statements)
references
References 70 publications
(39 reference statements)
6
67
0
Order By: Relevance
“…The IC 50 value of CaCl 2 was ~210 mM for A549 cells. 15 Final concentrations of CaCl 2 used with cells in transfection studies ranged from 1–60 mM (corresponding to the reported starting concentrations of 5–300 mM) which were far below this IC 50 value.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…The IC 50 value of CaCl 2 was ~210 mM for A549 cells. 15 Final concentrations of CaCl 2 used with cells in transfection studies ranged from 1–60 mM (corresponding to the reported starting concentrations of 5–300 mM) which were far below this IC 50 value.…”
Section: Discussionmentioning
confidence: 92%
“…15 Briefly, complexes were prepared by adding 10 µL (0.1 µg/µL) of DNA to 15 µL of PEI (polymer nitrogen to DNA phosphate (N/P) ratio of 10) or to 15 µL of TAT conjugates (at desired N/P ratios) followed by intensive pipetting. Fifteen microliters of DNase free water or known concentrations (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be attributed to the fact that although calcium was shown to condense copolymer/DNA complexes by interacting with both amines and phosphate, it also acted simultaneously as a competitive inhibitor of amine/phosphate interactions at high concentration. 41 Srinivasan et al showed that excessive Ca 2+ concentration (beyond 25 mM) led to particle aggregation and decreased transfection efficiency; therefore, the concentration of cations needs to be adequately controlled. 39 On the other hand, PA-I significantly outperformed PA in terms of transfection efficiency, in the presence of 15 mM Ca…”
Section: Transfection Efficiencymentioning
confidence: 99%